Address by Mrs Irina Bokova, Director-General of UNESCO on the occasion of the Language Resources and Evaluation Conference 2014; Reykjavík, 26 May 2014 - UNESCO. Director-General, 2009-2017 (Bokova, I.G.) (26 May 2014, 2014)
Electronic version only